2017
DOI: 10.9790/3008-1201018792
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use and Misuse Among Adults in Magwagwa Ward, Nyamira County in Kenya

Abstract: Self-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…This result was found to be harmonious with some studies [18, 21, 27], and contradicts with other studies [22, 23] when it comes to gender. Some studies showed no significant association of socio-demographic factors with the practice of SMA [22, 23, 27] and other studies showed educational level [12, 22, 26], age, [12, 28, 29] and socioeconomic status [12, 26] to have statistically significantly associated with SMA.…”
Section: Discussioncontrasting
confidence: 92%
“…This result was found to be harmonious with some studies [18, 21, 27], and contradicts with other studies [22, 23] when it comes to gender. Some studies showed no significant association of socio-demographic factors with the practice of SMA [22, 23, 27] and other studies showed educational level [12, 22, 26], age, [12, 28, 29] and socioeconomic status [12, 26] to have statistically significantly associated with SMA.…”
Section: Discussioncontrasting
confidence: 92%
“…The 40 studies included in this review were from 19 African countries and all five African sub‐regions: seven from Northern Africa [24–30], three from Central Africa [31–33], 14 from Western Africa [34–47], 15 from Eastern Africa [48–61] and one from Southern Africa [62] (Figure 2). Thirty‐seven studies were cross‐sectional surveys and three were mixed‐method (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies met all nine quality criteria in the assessment tool [48, 63, 64]. Twenty‐four studies showed a low risk of bias [25, 26, 28, 30, 32, 34, 36, 40, 42, 43, 45, 48–52, 54–56, 59–61, 63–65], 15 studies showed a moderate risk of bias [24, 27, 31, 35, 37–39, 41, 44, 46, 57, 58, 62, 66], and one study showed a high risk of bias [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, previous studies conducted in two different cities of Pakistan (Karachi, 80%; Peshawar, 69%) showed a higher prevalence of SMA than the present study [ 4 , 28 ]. In addition to this, studies performed in other developing countries, such as Kenya (60.0%), Nigeria (82.2%), Yemen (87.1%), and Saudi Arabia (40.8%) [ 32 , 33 , 34 , 35 ] also showed a higher prevalence of SMA by the public. The differences in the SMA rates may be due to ethnic diversity among the different populations and different healthcare systems in each of these countries.…”
Section: Discussionmentioning
confidence: 73%